Exploring Students’ Barriers to Code-Switching in English Classroom - Prastiwi, Retno; Septiyana, Linda; Suprihatin, Yeni; Setiyana, Leny (Universitas Pamulang, 2025)
Nowadays, studies on code-switching involving students have received limited focus, despite many research conducted on the university students’ code-switching. This study examines the contemporary issue of students’ barriers due to excessive dependence on code-switching in the English classroom. This phenomenological study employed a qualitative analysis technique and involved ten students from the English and Arabic departments of a state Islamic institution in East Lampung, Indonesia. The research data were acquired through observations and interviews with the participants. Additionally, the findings of this study indicate that a lot of students consider the social context, including the identity of the interlocutor and the situations code-switching occurs in the English classroom. Furthermore, most of students associated code-switching with the custom prevalent in their environment. This study also revealed that students consciously realize and admit barriers in the learning process. The barriers stem from the students’ excessive dependence on code-switching, hindering their ability to engage in tasks necessitating the usage of the target language. This study’s findings will offer significant insights for students to help reduce the continuing usage of code-switching by anticipating its future implications, which will assist lecturers in adjusting their approach to code-switching in the English learning process in each department.